KEARIFAN TRADISI MASYARAKAT DAYAK DEAH DI KALIMANTAN SELATAN - Asef Saefuddin (tuahtalino, 2019)
The problem which is discussed in this study is how does the form of the wisdom of Dayak Deah society tradition in South Kalimantan. This study aims to reveal the form of the wisdom of Dayak Deah society tradition in South Kalimantan. Dayak Deah society in South Kalimantan still preserves their custom in the form of wisdom tradition. Those tradition are giving birth tradition, marriage tradition, utterance fine tradition, and death ceremony tradition. Those heritage traditions are well kept to make them still exist. This study uses descriptive qualitative method to get information about the form of the wisdom of Dayak Deah society tradition in South Kalimantan deeply. The result shows the description about the form of the wisdom of Dayak Deah society tradition in South Kalimantan.